Relative Impacts of ENSO and Indian Ocean Dipole/Zonal Mode on Southern African Rainfall - Manatsa, Desmond (Department of Oceanography, 2014)
This thesis investigates the October to December (OND) rainfall variability over the mainland region of southeastern Africa in relation to El Niño Southern Oscillation (ENSO) and the Indian Ocean Dipole/Zonal Mode (IODZM) for the period 1950 to 1999. An empirical orthogonal function (EOF) analysis of OND rainfall field revealed that the north-south aligned areas of the eastern SADC are located in different covariability regions. This meridionally aligned dipole rainfall anomaly configuration is captured only in the dominant principal component (PC1) making it possible for the opposing rainfall anomalies of the two regions to have a common trigger. However, ENSO which has typically been invoked as the main cause for significant rainfall variability over this region cannot adequately explain this dipole rainfall anomaly pattern. The results of statistical analyses strongly indicate that positive Indian Ocean Dipole/Zonal Mode (IODZM) phase events lead to a rainfall dipole such that floods occur over the north east of the region (Tanzania) at the same time as droughts over the south east of the region (Zimbabwe, northern South Africa). On the other hand, negative IODZM phase events do not seem to lead to the reverse rainfall anomalies suggesting that the positive and negative rainfall dipoles may have rather different causes. Thus, contrary to conventional knowledge, the ENSO association to this dipole rainfall anomaly pattern is not robust but appears to be the result of the well known ENSO-IODZM connection. However, when analysed over 31-year overlapping segments, the results indicate that the sensitivity of this rainfall pattern to the IODZM is weakening from the 1990s onwards whereas that of ENSO appears to be strengthening.